Are the global economic policy uncertainties blocking the export flows of emerging markets? A heterogeneous panel SVAR analysis - Caglayan Aslan; Senay Acikgoz (Universitas Islam Indonesia, 2023)
Purpose – This paper examines the effect of global economic policy uncertainty (EPU) on emerging markets (EMs) export flows. Methods – This paper uses a structural panel vector autoregression modeling approach to capture country interdependencies and the likelihood that EMs’ responses are heterogeneous and dynamic. An unbalanced monthly panel data from 2003:01 to 2019:12 is used to estimate impulse responses and variance decompositions not only for the entire panel data but also for each EM. Findings – The results show that global EPU has a persistent and negative effect on exports, while foreign income and the exchange rate increase export volumes in EMs. Given the different responses of EMs to uncertainty shocks, the second-stage regression estimates suggest that greater sectoral export diversification in an EM can potentially reduce the unfavorable impact of global EPU on their export flows. Meanwhile, the higher technology content of exports leads to a multiplication of global EPU transmissions. Implication – These findings advance the literature by highlighting the importance of accounting for the transmission effect of global EPU in EMs by considering country heterogeneity. Originality – This is the sole paper examining the factors that mitigate or amplify GEPU impacts on export flows by estimating second-step ordinary least square equations.